Friday the 13th: The Empirics of Bad Luck - Jan Fidrmuc; J. D. Tena (Center for Economic Studies and ifo Institute (CESifo), 2014)
We use the UK Labor Force survey to investigate whether the socio-economic outcomes of people born on the 13th day of the month, and of those born on Friday the 13th, differ from the outcomes of people born on more auspicious days. In many European countries, including the UK, such days are considered unlucky. We consider outcomes that are unlikely to be affected by behavioral adjustments yet which are of considerable importance to one's quality of life: employment, earnings and marriage. We find no evidence that people born on the 13th or those born on Friday the 13th suffer any penalty that can be attributable to the inauspicious circumstances of their birth.
Keywords: J11; J21; J31; 330; superstition; employment; labor market; marriage